Comparison of two dose regimens of ibuprofen for the closure of patent ductus arteriosus in preterm newborns - Laura Vargas Dornelles; Andréa Lúcia Corso; Rita de Cássia Silveira; Renato Soibelmann Procianoy (Brazilian Society of Pediatrics, 2016)
Objective: To compare the efficacy of intravenous ibuprofen at high doses (20, 10, and 10 mg/kg/dose) and at low doses (10, 5, and 5 mg/kg/dose) in closure of the ductus arteriosus in preterm neonates. Methods: A cohort study with historic control of neonates who received high‐dose and low‐dose intravenous ibuprofen, from 2010 to 2013 in the neonatal inpatient unit, for closure of the ductus arteriosus, as documented by echocardiography. Secondary outcomes included number of ibuprofen cycles, incidence of bronchopulmonary dysplasia, necrotizing enterocolitis, change in renal function, and death. Results: Seventy‐seven patients received 3 doses of ibuprofen for the treatment of patent ductus arteriosus, 33 received high‐dose and 44 low‐dose therapy. The ductus closed after the first cycle in 25 (56.8%) low‐dose patients and in 17 (51.5%) high‐dose patients (p > 0.99). Sixteen patients received a second cycle of ibuprofen, and the ductus closed in 50% after low‐dose and in 60% after high‐dose therapy (p > 0.99). Seven patients required surgery for ductus closure, 13.6% in the low‐dose group and 3% in the high‐dose group (p = 0.22). Thirty‐nine patients developed bronchopulmonary dysplasia, 50% in the low‐dose group and 51.5% in the high‐dose group (p > 0.99). Twenty‐two (50%) low‐dose patients died vs 15 (45.5%) high‐dose patients (p = 0.86). Conclusions: There was no difference in closure of the ductus arteriosus or occurrence of adverse effects between the two dosing regimens.